PENGEMBANGAN FLIPBOOK MATEMATIKA DALAM PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS X PADA SMA NEGERI 2 PADANG - Rahmat, Hasyri; Suherman, Suherman (Jurnal Edukasi dan Penelitian Matematika, 2024)
One area of technology that is growing quickly in Indonesia is education technology. The use of technology in education aids in the process of helping students learn. One of the reasons for the continued low quality of education in Indonesia, particularly in mathematics, is the use of subpar teaching resources. Flipbooks, especially when used with sequential or sequential information, are thought to be able to enhance the quality of classroom learning in terms of students' ability to solve mathematical problems and autonomous learning. Flipbooks include textual content along with graphics, videos, and other engaging elements. Thus, the purpose of this research was to develop flipbook series and sequential materials that are both useful and effective. According to the Plomp, this kind of research is Research and Development (R&D).Keywords– Learning outcomes, Realistic Mathematics Education